Invariant Approximation Property for Subgroups - Kannan, K. (RGN Publications, 2021)
Analytic properties of invariant approximation property, studies analytic techniques from operator theory that encapsulate geometric properties of a group. We will study the invariant approximation property in various contexts. We shall show that it passes to subgroups.
Keywords: Uniform Roe algebras; Invariant approximation property; Rapid decay property